Peran Perawat Sebagai Edukator Kepada Pasien Rumah Sakit X - Hanipah Hanipah; Aisyah Nurjanah; Nur Saebah; Rafi Farizki; Hilyah Farhany Faradilla (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – The results of observations at the X hospital in Central Java revealed that there were not a few patients who experienced hopelessness so that the healing process became more difficult and longer due to negative patient perceptions. To overcome this, of course, requires the performance of components from hospital health including nurses to help recover patients through positive thinking. For this reason, this study wants to examine the role of nurses as educators for patients at Hospital X. The aim is to find out the role given by educational nurses to patients at Hospital X, Central Java. The research method used is descriptive quantitative with 50 respondents selected by purposive sampling and random sampling. Data collection procedures were carried out through observation, interview documentation, and distribution of questionnaires to the respondents. After the data is obtained, an in-depth analysis will be carried out so that it is known that the nurse educator provides a fairly positive role worth 55% in helping patients to have positive thoughts so that recovery and treatment time becomes more effective and efficient. Nevertheless, it is also known that nurse educators do not feel optimal in carrying out their performance due to several factors such as a lack of personnel in the team, training that has not been ongoing and so on which has resulted in their skills not developing rapidly.